Penerapan Cooperative Learning Tipe Think Pair Share Berbasis Budaya Mandailing dalam Pembelajaran Bahasa Indonesia: Penelitian - Akhirur Rhomadon Matondang; Erna Ikawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the application of the Mandailing culture-based Think Pair Share (TPS) type Cooperative Learning model in Indonesian learning at SDN No. 101390 Batang Pane 1 and describe the integration of Mandailing culture and student activity during learning. This study uses a descriptive approach with the research subjects of elementary school students and classroom teachers. Data collection techniques include observation, interviews, and documentation. The data obtained was analyzed in a qualitative descriptive manner through the stages of data reduction, data presentation, and conclusion drawn, and strengthened by triangulation techniques to maintain the validity of the data. The results of the study show that the Think Pair Share model can be applied well in Indonesian language learning. Teachers are able to carry out each stage of TPS in a sequential manner, namely the stages of thinking, pairing, and sharing. The integration of Mandailing culture is carried out through the use of folklore, examples of the daily life of the local community, and the application of the value of mutual cooperation (marsiadapari) in student discussion activities. This culture-based learning makes the material more contextual and easy for students to understand. In addition, student activeness and participation showed an increase, characterized by the courage to speak, involvement in discussions, and positive social interaction between students.